2015
DOI: 10.1074/jbc.m115.645846
|View full text |Cite
|
Sign up to set email alerts
|

Small Retinoprotective Peptides Reveal a Receptor-binding Region on Pigment Epithelium-derived Factor

Abstract: Background: Pigment epithelium-derived factor (PEDF) interacts with its receptor PEDF-R to exert cytoprotection. Results: Alanine scanning of a small fragment (17-mer) of PEDF reveals key interacting residues for binding PEDF-R and alternative retinoprotective peptide versions with higher efficacy. Conclusion: The 17-mer contains a novel PEDF-R binding region important for retinoprotection. Significance: Altered PEDF peptides could be exploited pharmacologically to improve protection of photoreceptors from deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(64 citation statements)
references
References 38 publications
7
57
0
Order By: Relevance
“…In the present study, there was also a decrease in corneal neovascularization that could be due to the antiangiogenic portion of the glycoprotein, the 34-mer-PEDF (Barnstable and Tombran-Tink, 2004; Becerra, 2008; Kenealey et al, 2015). It has been shown that PEDF blocks the survival, proliferation and migration of vascular endothelial cells by disrupting the pro-angiogenic action of vascular endothelial factor (VEGF), suppressing the expression of metalloproteinases (MMPs)-2 and-9 and upregulating Fas/Fas ligand (Haurigot et al, 2012; Matsui et al, 2012, Volpert et al, 2002).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In the present study, there was also a decrease in corneal neovascularization that could be due to the antiangiogenic portion of the glycoprotein, the 34-mer-PEDF (Barnstable and Tombran-Tink, 2004; Becerra, 2008; Kenealey et al, 2015). It has been shown that PEDF blocks the survival, proliferation and migration of vascular endothelial cells by disrupting the pro-angiogenic action of vascular endothelial factor (VEGF), suppressing the expression of metalloproteinases (MMPs)-2 and-9 and upregulating Fas/Fas ligand (Haurigot et al, 2012; Matsui et al, 2012, Volpert et al, 2002).…”
Section: Discussionsupporting
confidence: 54%
“…It appears to act through different receptors, including a PEDF receptor (PEDF-R), which has been shown to interact with the N-terminal portion of the PEDF molecule, mediating its neurotrophic effect and neuronal differentiating activity (Kenealey et al, 2015; Notari et al, 2006; Subramanian et al, 2010). Although the mechanism by which PEDF+DHA promotes nerve regeneration in the rabbit is not completely understood, we have previously found that corneal epithelial cells express a PEDF-R linked to phospholipase activity and that the peptide 44-mer-PEDF (which has neurotrophic properties), in conjunction with DHA, also increases corneal nerve regeneration (He et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…65 The neuroprotective effect of PEDF has been demonstrated by observations that injection of PEDF protein peptides into the eye of the C3H/HeN retinal degeneration 1 (rd1) mouse confers strong neuroprotection to degenerating photoreceptors. 66 This rescue from photoreceptor cell death has been attributed to a decrease in intracellular Ca 2+ concentrations and consequently to a decrease in calpain activity induced by PEDF. 67 Further confirmation of the neurotrophic effects of PEDF has been shown by inhibition of photoreceptor apoptosis following lentivirus-mediated retinal gene transfer of PEDF into the subretinal space of the RCS rat.…”
Section: Müller Glia Are An Important Source Of Neurotrophins Within mentioning
confidence: 99%
“…PEDF-R is distributed in the inner segments of photoreceptors [ 21 , 29 ]. Small PEDF peptides from the neurotrophic domain bind PEDF-R and exhibit survival activities on retinal cells [ 21 , 23 , 31 ]. In this regard, the protective capacity of 17-mer (a peptide of 17 amino acids spanning positions 98–114 of the human PEDF sequence), and 17-mer[H105A] (a derived 17-mer peptide with single residue substitution to alanine on position 105 and improved retinoprotective activity) has been recently described in vivo and ex vivo in the rd1 , rd10 and Mitf mouse models of inherited genetic retinal degeneration [ 21 , 23 , 32 ].…”
Section: Introductionmentioning
confidence: 99%